Effect of HIV‐1 Infection on Angiopoietin 1 and 2 Levels and Measures of Microvascular and Macrovascular Endothelial Dysfunction - Anjali B. Thakkar; Yifei Ma; Mark Dela Cruz; Yuaner Wu; Victor Arechiga; Shreya Swaminathan; Peter Ganz; Alan H. B. Wu; Rebecca Scherzer; Steven Deeks; Priscilla Y. Hsue (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Individuals infected with HIV have an increased risk of developing cardiovascular disease; yet, the underlying mechanisms remain unknown. Recent evidence has implicated the Tie‐2 tyrosine kinase receptor system and its associated ligands ANG1 (angiopoietin 1) and ANG2 (angiopoietin 2) in maintaining vascular homeostasis. In the general population, lower ANG1 levels and higher ANG2 levels are strongly correlated with the development of cardiovascular disease. In this study, we aim to investigate the associations of HIV infection with angiopoietin levels and endothelial dysfunction. Methods and Results In this cross‐sectional study, we compared measures of ANG1, ANG2, and endothelial dysfunction using flow‐mediated vasodilation of the brachial artery in 39 untreated subjects infected with HIV, 47 treated subjects infected with HIV, and 46 uninfected subjects from the SCOPE (Observational Study of the Consequences of the Protease Inhibitor Era) cohort. Compared with uninfected controls, treated individuals infected with HIV had 53.1% lower mean ANG1 levels (P<0.01) and similar ANG2 levels. On the other hand, untreated individuals infected with HIV had similar ANG1 levels, and 29.2% had higher ANG2 levels (P<0.01) compared with uninfected controls. When compared with individuals with untreated HIV infection, those with treated HIV infection had 56% lower ANG1 levels (P<0.01) and 22% lower ANG2 levels (P<0.01).Both treated and untreated HIV infection were associated with significant impairment in hyperemic velocity, a key measure of microvascular dysfunction (median 61 versus 72 cm/s, P<0.01), compared with uninfected controls (median 73 cm/s). This difference persisted after adjustment for ANG1 and ANG2 levels. Interestingly, when compared with untreated individuals infected with HIV, treated individuals infected with HIV had worse hyperemic velocity (−12.35 cm/s, P=0.05). In contrast, HIV status, ANG1 levels, and ANG2 levels were not associated with macrovascular dysfunction as measured by flow‐mediated dilatation and brachial artery diameter, 2 other measures of vascular homeostasis. Conclusions HIV infection affects the balance between levels of ANG1 and ANG2 and may disturb endothelial homeostasis through disruption of vascular homeostasis. Individuals with treated HIV had decreased ANG1 levels and similar ANG2 levels, whereas individuals with untreated HIV had similar ANG1 levels and increased ANG2 levels, suggesting that treatment status may alter the balance between ANG1 and ANG2. HIV also promotes endothelial dysfunction via impairment of microvascular dysfunction, independent of the Tie‐2 receptor system; the finding of worse microvascular dysfunction in the setting of treated HIV infection may reflect the impact of viral persistence on the microvasculature or toxicities of specific antiretroviral regimens. Further research to clarify the mechanism of HIV‐mediated endothelial dysfunction is necessary to advance treatment of cardiovascular complications of HIV infection.